Verification of a solvent optimization approach for postcombustion CO2 capture using commercial alkanolamines. (January 2016) - Li, Zhiwei; Chen, Shiaoguo; Hopkinson, David; Luebke, David
Highlights: A phase equilibrium approach for optimization of conceptual solvents is verified. A conventional absorption based postcombustion CO2 capture process is applied. Verification is based on process simulation with commercial solvents, AMP and MDEA. An optimal lean loading exists for a least separation energy demand. An optimal inlet solvent temperature of a stripper is approved. Abstract: This paper verified a phase equilibrium approach for optimization of conceptual solvents by using process simulations of commercial solvents N-methyl-diethanolamine (MDEA) and 2-amino-2-methyl-1-propanol (AMP) aqueous solution, for a conventional absorption/desorption based postcombustion CO2 capture process. The simulated total heat/total equivalent work for the investigated tertiary/hindered amines has the same trends as those based on the phase equilibrium approach for conceptual solvents with the same heat of reactions. Moreover, the simulated CO2 working capacities for the commercial solvents agree well with those obtained with the phase equilibrium approach for the corresponding conceptual solvents, verifying the phase equilibrium approach. Results of parametric tests using the AMP aqueous solution illustrate that there is an optimal lean loading for the lean solution and an optimal temperature for the stripper inlet solvent to achieve the least total equivalent work/total heat.